Quantitative angiographic haemodynamic evaluation of bypasses for complex aneurysms: a preliminary study. Issue 1 (12th October 2021) - Lu, Junlin; Xue, Chao; Hu, Xulin; Zhao, Yuanli; Zhang, Dong; Chen, Xiaolin; Zhao, Ji Zong
Abstract : Objective: Open microsurgery, often with bypass techniques, is indispensable for complex aneurysms. To date, it remains unknown whether arterial anatomy or quantitative blood flow measurements can predict insufficient flow-related stroke (IRS). The present study aimed to evaluate the risk factors for IRS in patients treated with open microsurgery with bypass procedures for complex internal carotid artery aneurysms. Methods: Patients with complex aneurysms undergoing bypass surgery were retrospectively reviewed. The recipient/donor flow index (RDFI) was preoperatively evaluated using colour-coding angiography. RDFI was defined as the ratio of the cerebral blood volume of the recipient and donor arteries. The sizes of the recipient and donor arteries were measured. The recipient/donor diameter index (RDDI) was then calculated. IRS was defined as the presence of new postoperative neurological deficits and infarction on postoperative CT scans. We assessed the association between RDFI and other variables and the IRS. Results: Twenty patients (38±12 years) were analysed. IRS was observed in 12 patients (60%). Patients with postoperative IRS had a higher RDFI than those without postoperative IRS (p<0.001). RDDI was not significantly different between patients with and without IRS (p=0.905). Patients with RDFI >2.3 were more likely to develop IRS (p<0.001). Conclusion: Quantitative digital subtraction angiography enables preoperative evaluation of cerebral blood volume. RDFI >2.3, rather than RDDI, was significantly associated with postoperative IRS. This preoperative evaluation allows appropriate decisions regarding the treatment strategy for preventing postoperative IRS.